Responsiveness and meaningful improvement of mobility measures following MS rehabilitation. (13th November 2018) - Baert, Ilse; Smedal, Tori; Kalron, Alon; Rasova, Kamila; Heric-Mansrud, Adnan; Ehling, Rainer; Elorriaga Minguez, Iratxe; Nedeljkovic, Una; Tacchino, Andrea; Hellinckx, Peter; Adriaenssens, Greet; Stachowiak, Gosia; et al.
Abstract : Objective: To determine responsiveness of functional mobility measures, and provide reference values for clinically meaningful improvements, according to disability level, in persons with multiple sclerosis (pwMS) in response to physical rehabilitation. Methods: Thirteen mobility measures (clinician- and patient-reported) were assessed before and after rehabilitation in 191 pwMS from 17 international centers (European and United States). Combined anchor- and distribution-based methods were used. A global rating of change scale, from patients' and therapists' perspective, served as external criteria when determining the area under the receiver operating characteristic curve (AUC), the minimally important change (MIC), and the smallest real change (SRC). Patients were stratified into 2 subgroups based on disability level (Expanded Disability Status Scale score ⩽4 [n = 72], >4 [n = 119]). Results: The Multiple Sclerosis Walking Scale–12, physical subscale of the Multiple Sclerosis Impact Scale–29 (especially for the mildly disabled pwMS), Rivermead Mobility Index, and 5-repetition sit-to-stand test (especially for the moderately to severely disabled pwMS) were the most sensitive measures in detecting improvements in mobility. Findings were determined once the AUC (95% confidence interval) was above 0.5, MIC was greater than SRC, and results were comparable from the patient and therapist perspective. Conclusions: Responsiveness, clinically meaningful improvement, and real changes of frequently used mobility measures were calculated, showing great heterogeneity, and were dependent on disability level in pwMS.